From Vietnamese plants to a biflavonoid that relieves inflammation by triggering the lipid mediator class switch to resolution - Tran Thi Van Anh; Alilou Mostafa; Zhigang Rao; Simona Pace; Stefan Schwaiger; Christian Kretzer; Veronika Temml; Carsten Giesel; Paul M. Jordan; Rossella Bilancia; Christina Weinigel; Silke Rummler; et al. (Elsevier, 2021)
Chronic inflammation results from excessive pro-inflammatory signaling and the failure to resolve the inflammatory reaction. Lipid mediators orchestrate both the initiation and resolution of inflammation. Switching from pro-inflammatory to pro-resolving lipid mediator biosynthesis is considered as efficient strategy to relieve chronic inflammation, though drug candidates exhibiting such features are unknown. Starting from a library of Vietnamese medical plant extracts, we identified isomers of the biflavanoid 8-methylsocotrin-4'-ol from Dracaena cambodiana, which limit inflammation by targeting 5-lipoxygenase and switching the lipid mediator profile from leukotrienes to specialized pro-resolving mediators (SPM). Elucidation of the absolute configurations of 8-methylsocotrin-4'-ol revealed the 2S,γS-isomer being most active, and molecular docking studies suggest that the compound binds to an allosteric site between the 5-lipoxygenase subdomains. We identified additional subordinate targets within lipid mediator biosynthesis, including microsomal prostaglandin E2 synthase-1. Leukotriene production is efficiently suppressed in activated human neutrophils, macrophages, and blood, while the induction of SPM biosynthesis is restricted to M2 macrophages. The shift from leukotrienes to SPM was also evident in mouse peritonitis in vivo and accompanied by a substantial decrease in immune cell infiltration. In summary, we disclose a promising drug candidate that combines potent 5-lipoxygenase inhibition with the favorable reprogramming of lipid mediator profiles.